REVIEW: PENDEKATAN PENILAIAN KINERJA AGROINDUSTRI TEH MENGGUNAKAN MODEL SISTEM DINAMIK - Aulia Briliantina; Bambang Herry Purnomo; Ida Bagus Suryaningrat (Faculty of Agricultural Technology, University of Jember, 2016)
The best applying practice of performance management can lead to increase business competitiveness. Improved performance of tea agroindustry as a part to overcome the problems of declining quality and productivity of tea agroindustry. The objective of this study was to describe of how performance assesment systems that has been conducted to achieve success areas of tea agroindustry and design of performance dynamic model of tea agroindustry. Performance measurement system structuralization based on IDPMS (Integrated Dynamic Performance Measurement System) model and identification area of success and performance assesment using questionnaires guidelines PMQ (Performance Measurement Questionnaire). Design of performance dynamic model using powersim software. Keywords: tea agroindustry, system dynamics, performance assesment, IDPMS